2011
DOI: 10.1111/j.1752-4571.2010.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary principles and their practical application

Abstract: Evolutionary principles are now routinely incorporated into medicine and agriculture. Examples include the design of treatments that slow the evolution of resistance by weeds, pests, and pathogens, and the design of breeding programs that maximize crop yield or quality. Evolutionary principles are also increasingly incorporated into conservation biology, natural resource management, and environmental science. Examples include the protection of small and isolated populations from inbreeding depression, the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
265
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(266 citation statements)
references
References 277 publications
1
265
0
Order By: Relevance
“…Therefore, understanding the origins, architecture, and maintenance of genetic variation is critical for predicting the short‐ and long‐term responses of populations, communities, and ecosystems to novel and changing environments (Hendry et al., 2011; Lankau, Jørgensen, Harris, & Sih, 2011). …”
Section: Intraspecific Variation Is Critical For Population Dynamicsmentioning
confidence: 99%
“…Therefore, understanding the origins, architecture, and maintenance of genetic variation is critical for predicting the short‐ and long‐term responses of populations, communities, and ecosystems to novel and changing environments (Hendry et al., 2011; Lankau, Jørgensen, Harris, & Sih, 2011). …”
Section: Intraspecific Variation Is Critical For Population Dynamicsmentioning
confidence: 99%
“…A key concern raised by evolutionary biologists is the general lack of consideration given by managers to how their management practices can act as a selection pressure on wild populations (Hendry et al., 2011; Smith et al., 2014). This is particularly relevant for invasive species management, where the evidence from agricultural science can inform risk assessments for management practice that might promote the evolution of resistance to the toxins used to control pest species (Neve, Busi, Renton, & Vila‐Aiub, 2014; Tabashnik, Brevault, & Carriere, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some authors have reported that managers often view species as fixed entities that do not change (Ashley et al., 2003), or believe that evolution happens too slowly to be relevant to management practices (Kinnison, Hendry, & Stockwell, 2007; Smith et al., 2014). It has also been suggested that managers have risk adverse attitudes to changing their management practices, viewing the manipulation of evolutionary forces as potentially disrupting the integrity of natural processes (Hendry et al., 2011; Smith et al., 2014). Concerns have also been raised that the actions of many managers remain guided by largely outdated or misinterpreted ideas, for example, anxiety about the risk of outbreeding depression when mixing populations, despite growing evidence that the risks have been overstated (Frankham, 2015; Frankham et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Irrespectively of its basis, the changes in the protective mechanisms level enhance survivorship chance of a population under stressing conditions (Ho and Burggren 2010;Hendry et al 2011;Feil and Fraga 2012). The experiment conducted on an unique isolated Cd-selected population of S. exigua gave us the opportunity to observe the changes under controlled conditions.…”
Section: Discussionmentioning
confidence: 99%